Preparation and characterization of biodegradable and hemocompatible copolymers - Park, Ji Hoon; Park, Seung Hun; Park, Joon Yeong; Ju, Hyeon Jin; Ji, Yun Bae; Kim, Jae Ho; Min, Byoung Hyun; Kim, Moon Suk (Reactive and Functional Polymers, 2020)
In this study, we developed biodegradable polyesters with hemocompatibility and anti-thrombotic functions. First, we synthesized 3-benzyloxymethyl-6-methyl-1,4-dioxane-2,5-dione (LA-Bz). The ring opening polymerization of ε-caprolactone (CL), L-lactide (LA), and LA-Bz monomers provided poly(ε-caprolactone-ran-L-lactide-ran-3-benzyloxymethyl lactide) (PCLA-Bz) copolymers. Poly(ε-caprolactone-ran-L-lactide) (PCLA) was prepared as a control biodegradable copolymer. Subsequent deprotective benzyl reactions of PCLA-Bz and additional reactions with glutaric anhydride yielded PCLA copolymers with COOH pendant groups (PCLA-COOH). Afterward, methoxypolyethylene glycol (PCLA-MPEG) or heparin (PCLA-heparin) as an anti-thrombotic group was introduced in the pendant position of PCLA. The in vitro degradation and mechanical properties of PCLA, PCLA-COOH, PCLA-MPEG, and PCLA-heparin were examined over 8 weeks. In the hemocompatibility testing, PCLA-COOH, PCLA-MPEG, and PCLA-heparin exhibited hemocompatibility with little adherence of platelets. In addition, PCLA-heparin exhibited significantly reduced platelet adhesion and enhanced blood stability and thrombin inactivation. These results show that the introduction of anti-thrombotic groups in the pendant position of PCLA represents a useful approach to prepare biodegradable and hemocompatible copolymers.
Keywords: Additional reactions; Anti-thrombosis; Biodegradable copolymers; Biodegradable polyesters; Functionalizations; Glutaric anhydride; Hemocompatibility; Methoxypolyethylene glycol; Anti-thrombosis; Biodegradation; Functionalization; Hemocompatibility; Polyesters